1998
DOI: 10.1021/la9712449
|View full text |Cite
|
Sign up to set email alerts
|

Inner-Sphere and Outer-Sphere Complexation of a Polycarboxylic Acid at the Water−Boehmite (γ-AlOOH) Interface:  A Combined Potentiometric and IR Spectroscopic Study

Abstract: Speciation and equilibria of 1,2,4,5-benzenetetracarboxylate (pyromellitate) at the water−boehmite (γ-AlOOH) interface were studied in 0.1 M Na(Cl) at 298 K. Surface equilibrium analyses were based upon potentiometric and adsorption measurements in the range 4.5 < pH < 10.0. To characterize the surface complexes at the molecular level, attenuated total reflectance infrared spectra were recorded. The IR data provided information on the structure and composition of the complexes. This information could then be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
63
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 14 publications
14
63
0
Order By: Relevance
“…Figure 1 shows that the benzene carboxylic acids have a higher affinity for the goethite surface than kaolinite. The adsorption edges for phthalic acid onto goethite found in this study are similar to those found in previous studies (17,18,(21)(22)(23)(24).…”
Section: Modeling Coadsorption Of Anthracene and Phthalatesupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 1 shows that the benzene carboxylic acids have a higher affinity for the goethite surface than kaolinite. The adsorption edges for phthalic acid onto goethite found in this study are similar to those found in previous studies (17,18,(21)(22)(23)(24).…”
Section: Modeling Coadsorption Of Anthracene and Phthalatesupporting
confidence: 90%
“…Extended constant capacitance models have been used by Persson and coworkers (17)(18)(19) to describe the adsorption of benzene carboxylic acids onto a number of different surfaces. An ECCM allows adsorption to occur in two planes: "strongly" bound ions adsorb at the surface plane (0-plane) as inner-sphere complexes, and "weakly" bound ions adsorb in an outer plane (β-plane), separated from the surface by at least one layer of water molecules.…”
Section: Modeling Of the Adsorption Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, at low pH inner sphere complexes are found to be important for the binding of organic material (Gu et al, 1995;Kaiser et al, 1997;Nordin et al, 1998). This can be explained by the changes in electrical energy.…”
Section: Discussionmentioning
confidence: 99%
“…Zachara et al (1995) found that, at pH • 5, Co(II)EDTA adsorption on goethite and aquifer sands is followed by significant Co(II)EDTA dissociation within 30 minutes. Sigg (1996, 1997) (Chisholm-Brause et al, 1990;Roe et al, 1991;Manceau et al, 1992;Bargar et al, 1996;1997a,b,d; (Nordin et al, 1997;Nordin et al, 1998;Persson et al, 1998a;Persson et al, 1998b).…”
Section: Previous Workmentioning
confidence: 99%